Harmonisation of biosecurity laws in the Pacific - Secretariat of the Pacific Community (Secretariat of the Pacific Community (SPC), 2010)
Given the importance of effective biosecurity systems for protecting plant, animal and human health, environments and livelihoods, PICTs are urged to review and update all their existing legislation that deals with the protection of livelihoods and the environment...